Prevalence of Physical Fitness Among School Children in Vadodara City - Dharmang D Vyas; Dr. Madhavan Iyengar; Bhavana Gadhavi (The Bioscan, 2025)
This study investigates the prevalence of physical fitness among school children in Vadodara City. Utilizing a cross-sectional survey approach, we assessed physical fitness levels through a series of standardized tests and questionnaires. The study aims to understand fitness patterns and identify factors influencing physical fitness among children. Results reveal varying levels of fitness and highlight areas for potential improvement. The findings provide valuable insights for policymakers, educators, and health professionals to promote physical activity among school children.